Factors Affecting Time to Suicidal Resolution for Depressed Inpatients During Acute Treatment With Fluoxetine. Issue 4 (July 2020) - Lin, Ching-Hua; Su, Shu-Fang; Chou, Li-Shiu; Huang, Chun-Jen
Abstract : Supplemental digital content is available in the text.